Synergistic effect of extracellular polymeric substances and carbon layer on electron utilization of Fe@C during anaerobic treatment of refractory wastewater - Xu, Hui (2023)
Nano zero-valent iron (NZVI) has been widely used to improve refractory wastewater treatment. However, the rapid dissolution of NZVI causes a waste of resources and an unstable bioaugmentation. Herein, to verify the essential role of slow release of NZVI on biological systems, a core-shell structured Fe@C composite was developed to demonstrate the long-term feasibility of Fe@C for enhancing azo dye biodegradation in comparison to a mixture of NZVI and carbon powder (Fe+C). The 150 days of long-term reactor operation showed that, although both Fe@C and Fe+C enhanced azo dye degradation, the former achieved a better performance than the latter. The strengthening effect of Fe@C was also more durable and stable than Fe+C. It may be due to the fact that the carbon layer of Fe@C could interact with extracellular polymeric substances (EPS) through physical adsorption and chemical bonding to form a stable buffer to regulate NZVI dissolution. The buffer layer could not only regulate the attack of H+ on NZVI to reduce its dissolution rate but also complex released Fe2+ and neutralize OH- to alleviate the passivation layer formed on the NZVI surface. Moreover, microbial community analysis indicated that both Fe@C and Fe+C increased the abundance of fermentative bacteria (e.g., Bacteroidetes_vadinHA17, Propionicicella) and methanogens (e.g., Methanobacterium), but only Fe@C promoted the growth of azo dye degraders (e.g., Clostridium, Geobacter). Metatranscriptomic analysis further revealed that only Fe@C could substantially stimulate the expression of azoreductase and redox mediator (e.g., riboflavin, ubiquinone) biosynthesis involved in the extracellular degradation of azo dye. This work provides novel insights into the bioaugmentation of Fe@C for refractory wastewater treatment.